Blockchain-Assisted Framework for Improving the Taxation System of Pakistan - Muhammad Younas; Shahbaz Ahmad; Dr. Ahmad Khan; Nasir Khan (Dialogue Social Science Review (DSSR), 2025)
Pakistan tax system is weak, plagued with issue of corruption, and high tax gap which prevents the country’s growth. This paper seeks to discuss how blockchain technology can address these challenges through a permissioned blockchain model involving the Ministry of Finance, tax authorities, and the credit institutions. It is recommended that Public DLT be adopted for improved transparency with real time Tax Compliance Data being shared. This framework shares economic processing based on smart contracts by controlling tax calculations, refunds, and penalties that involve little human interaction and therefore less chance of fraud or mistakes. With reference to the proposed system, the utilization of blockchain is expected to provide authoritative and credible records of tax that can concurrently identify potential frauds for investigation. New business mechanisms that the popularized distributed database technology ‘Blockchain’ can assist in eliminating corruption, non-transparent, and slow-processing nature of the tax system and minimize the possibility of data fraud. It shows how through utilizing aspects of the blockchain technology, the work of taxes may be organized in a far efficient manner, how compliance may be encouraged and how Pakistan may benefit naturally from the ingenious concept. It ends on the call for both policy changes and technology advancements in demanding a social acceptance to support the application of blockchain as a tool for improving the nation's tax governance system.